Immunocompromised Children with Severe Adenoviral Respiratory Infection - Joanna C. Tylka; Michael C. McCrory; Shira J. Gertz; Jason W. Custer; Michael C. Spaeder (Critical Care Research and Practice)
Purpose. To investigate the impact of severe respiratory adenoviral infection on morbidity and case fatality in immunocompromised children. Methods. Combined retrospective-prospective cohort study of patients admitted to the intensive care unit (ICU) in four children’s hospitals with severe adenoviral respiratory infection and an immunocompromised state between August 2009 and October 2013. We performed a secondary case control analysis, matching our cohort 1 : 1 by age and severity of illness score with immunocompetent patients also with severe respiratory adenoviral infection. Results. Nineteen immunocompromised patients were included in our analysis. Eleven patients (58%) did not survive to hospital discharge. Case fatality was associated with cause of immunocompromised state (p=0.015), multiple organ dysfunction syndrome (p=0.001), requirement of renal replacement therapy (p=0.01), ICU admission severity of illness score (p=0.011), and treatment with cidofovir (p=0.005). Immunocompromised patients were more likely than matched controls to have multiple organ dysfunction syndrome (p=0.01), require renal replacement therapy (p=0.02), and not survive to hospital discharge (p=0.004). One year after infection, 43% of immunocompromised survivors required chronic mechanical ventilator support. Conclusions. There is substantial case fatality as well as short- and long-term morbidity associated with severe adenoviral respiratory infection in immunocompromised children.